Comparison of the McGRATHTM Video Laryngoscope and Macintosh Laryngoscope for Orotracheal Intubation in a Simulated Difficult Airway Scenario: An Open-Label, Randomized Clinical Trial - Kim, Jong-Yeop; Park, Seonghyeok; Oh, Minho; Choi, Jong-Bun; John, Hyun-Ji; Lee, Soo-Kyung; Choi, Yi-Hwa (Medicina (Kaunas, Lithuania), 2023)
Background and Objectives: Difficult intubation, which may be encountered unexpectedly during anesthesia, can increase patients’ morbidity and mortality. The McGRATH video laryngoscope is known to provide improved laryngeal visibility in patients with difficult or normal airways. The purpose of this study was to evaluate the efficacy of the McGRATH video laryngoscope for orotracheal intubation compared with that of conventional Macintosh laryngoscopes in simulated difficult airway scenarios. Materials and Methods: In this randomized controlled trial, patients who were scheduled for surgery under general anesthesia requiring orotracheal intubation were assigned to the Macintosh laryngoscope (n = 50) or McGRATH video laryngoscope (n = 45) groups. In this study, to create a simulated difficult airway condition, the subjects performed manual in-line stabilization and applied a soft cervical collar. The primary outcome was the rate of successful intubation within 30 s. The time required for an intubation, glottis grade, intubation difficulty scale (IDS score), the subjective ease of intubation, and optimal external laryngeal manipulation (OLEM) were evaluated. In addition, complications caused by each blade were investigated. Results: The intubation success rate within 30 s was not significantly different between the two groups (44 (88.0%) vs. 36 (80.0%), p = 0.286). The glottic grade was better in the McGRATH group than in the Macintosh group (p = 0.029), but neither the intubation time (26.3 ± 8.2 s vs. 24.2 ± 5.0 s, p = 0.134) nor the rates of oral bleeding (2 (4.0%) vs. 0 (0.0%)) and tooth injury (0 (0.0%) vs. 1 (2.2%)) were significantly different between the two groups. Conclusions: The use of the McGRATH video laryngoscope did not improve the intubation success rate or shorten the intubation time. However, the McGRATH video laryngoscope provided a better glottis view than the conventional Macintosh laryngoscope in patients with a simulated difficult airway.